Quality of work life and factors associated with it among elderly workers in Sri Lanka - Niluka Gunathilaka; Manuj C. Weerasinghe; Dulani Samaranayake (College of Community Physicians of Sri Lanka, 2024)
Introduction: The quality of work life (QoWL) of the elderly worke r becomes an important concept which needs to be assessed and improved with the increase of elderly population as their engagement in the workforce is inevitable. Objectives: To assess the prevalence and associated factors of QoW L among the elderly workers in Sri Lanka Methods: A cross-sectional survey study was conducted among el derly workers selected using multi-stage cluster sampling from Gampaha District. The QoWL was assessed using newly developed and validated Quality of Work Life Scale Elderly Workers. Factors associated with good QoWL were assessed through interviewer-administered questionnaire. Using a consensus reached cutoff mark, QoWL was dichotomized into 'good' and 'poor'. Data were analysed with descriptive statistics and factors associated with good QoWL were determined using bivariate analysis with Chi- squared test and multivariate analysis with multiple logistic regression. Results: The study included 835 elderly workers and the mean  score for total QoWL was 119.42 (SD=12.18). Prevalence of good QoWL among the elderly workers was 32.1% (95%  CI=29.0, 35.3). Good QoWL was significantly associated with multiple factors, such as personal, work related and p sychosocial factors. In the multivariate analysis, factors significantly associated with good QoWL of elder workers  were earning more than LKR 30,000 per month, having properties as an income generation method, engaging in a j ob before age 60 years, job helping to have social interaction, having adequate social support and engaging in political  activities. Spending on own food, having arthritis, experiencing work related accidents and occupational engagement  to support the family were negatively associated with good QoWL. Conclusions & Recommendations: The QoWL of elderly worke rs was at a low level and needs improvement interventions. Employees as well as policymakers should develop a nd implement appropriate strategies to improve their QoWL.